The Implementation of the Juvenile Justice System in Terrorism: Indonesia Case - Rd. Yudi Anton Rikmadani; Puguh Aji Hari Setiawan (University of Jember, Indonesia, 2022)
ABSTRACT: This research aims to review the right to child protection as well as the implementation of the Juvenile Criminal Justice System (SPPA) based on court rulings. Behind the research is concern about the increasing number of children involved in terrorist networks in Indonesia. Some of them have been sentenced to prison for terrorism plots. The implementation of the SPPA Act and the PA Act has become a reference for law enforcement in addition to counter-terrorism legislation. The crime of terrorism is a crime that must be addressed immediately because it threatens the state, but the state remains obliged to ensure the fulfillment of the right to child protection during the judicial process with special protection. With the involvement of a child that is in relevance to the child protection act, it is a complex matter that needs to be resolved with a special analysis of law, due to its nature. This study examines court rulings with normative juridical methods to get significantly achieved results. In addition, this study also adds secondary resources such as article journals, books, reports, and any source that has relevance to the study. The results of the study found that the special protection of children in the Crime of Terrorism has not been met, by not considering the child as a victim, because of the actions he did the influence of persuasion as revealed in court. In addition, law enforcement does not seek diversion as mandated in the SPPA. To conclude the court's decision does not consider the regulations on PA and has not fully implemented the SPPA. KEYWORDS: Legislation on Terrorism, Children's Rights, Law Enforcement, Juvenile Justice.